MARKETING STRATEGY FOR ECOTOURISM PRODUCTS IN LABUAN BAJO, EAST NUSA TENGGARA - Adi Husnaini (Politeknik Pariwisata NHI Bandung, 2023)
Ecotourism is part of sustainable tourism, where special attention is needed regarding environmental, economic, and social sustainability. Sustainable tourism is very much needed in the current era in order to preserve the nature and culture of an area. Sustainable tourism also involves the community fully, so that the impacts can be felt fully by the community directly. The purpose of this paper is to determine the internal and external factors needed to build a marketing strategy at the two research locations as well as to formulate a strategy based on SWOT analysis. The method used is descriptive-qualitative, using interviews, observation, and literature study, using the SWOT analysis technique. The results of this study show that there are several marketing programs that can be implemented in research locations, starting with product packaging, promotion, repositioning, and improving tourism services. Ecotourism destinations, learning from the benchmarking choices of researchers, and targeted marketing are aimed at special interest tourists. A visitor limit is being implemented with the goal of adjusting to the capacity of the conservation environment. so that the marketing strategy that is carried out should not invite mass tourism. However, collaboration and participation from other tourism actors are also needed in the promotion and management of destinations. Keywords: Environmental analysis, resources, ecotourism